FACTORS INFLUENCING PURCHASE INTENTION AND ACTUAL PURCHASE OF FREE TO PLAY GAMES: THE CASE OF VALORANT GAMES - Rabulizat, Tritanio Nizar; Chairy, Chairy; Rahmiati, Filda; Goenadhi, Felix (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2024)
Pasar game terus berkembang selama bertahun-tahun, menyumbang pendapatan signifikan dari penjualan